The Expressionist Moment: Heym, Trakl and the Problem of the Modern - James Rolleston (Studies in 20th & 21st Century Literature, 1976)
Hugo Friedrich's genealogical and normative theory of modern poetry is contrasted with Michel Foucault's essentially static formulations of man's self-creating posture at the centre of a world without transcendence. The role of history and history- making in the modern consciousness is then viewed from the perspective of the early Expressionist poets, Georg Heym (1887-1912) and Georg Trakl (1887-1914). Both writers saw the tradition of Romantic individualism as dead yet persisting in an aimless afterlife, but their responses were antithetical. Trakl, using his personal experience as an emblematic image of the end, reorchestrated the myths and depravities of tradition into a structure that includes its own destruction. Heym's reiterated evocations of sickness and apocalyptic paralysis reduce poetic tradition to the empty rhythm of anonymous individuality.
Keywords: Georg Heym; Georg Trakl; Hugo Friedrich; Michel Foucault; Romantic individualism; poetic tradition; normative theory of modern poetry; Expressionist